2022
DOI: 10.1111/jph.13123
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and morphological characteristics of Uromycladium falcatariae, the fungal pathogen that causes gall rust epidemics of Falcataria moluccana in Indonesia

Abstract: Falcataria moluccana (Miq.) Barneby & J.W. Grimes (syn. Paraserianthes falcataria [L.] I.C. Nielsen), locally known as 'sengon', belongs to the family of Fabaceae. The tree is one of the most important forest commodities in Indonesia with wood production being the third-highest after acacias and eucalyptus (Badan Pusat Statistik, 2020). Although the cultivation area is widespread in Java,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The status of gall rust disease incidence and severity in sengon plants were widespread and very severe, of which could reach 100% (Darwiati and Anggraeni 2018;Firdaus et al 2019;Rahayu et al 2020;Syarifuddin et al 2021). A molecular study identified the gall rust pathogen in sengon and changed the name from Uromycladium tepperianum to U. falcatariae (Doungsa-ard et al 2015;Doungsa-ard et al 2018;Lelana et al 2022). Uromycladium falcatariae is an obligate parasite that can grow and multiply if it remains in contact with its host plant.…”
Section: Introductionmentioning
confidence: 99%
“…The status of gall rust disease incidence and severity in sengon plants were widespread and very severe, of which could reach 100% (Darwiati and Anggraeni 2018;Firdaus et al 2019;Rahayu et al 2020;Syarifuddin et al 2021). A molecular study identified the gall rust pathogen in sengon and changed the name from Uromycladium tepperianum to U. falcatariae (Doungsa-ard et al 2015;Doungsa-ard et al 2018;Lelana et al 2022). Uromycladium falcatariae is an obligate parasite that can grow and multiply if it remains in contact with its host plant.…”
Section: Introductionmentioning
confidence: 99%